2020
DOI: 10.1007/s11056-020-09813-2
|View full text |Cite|
|
Sign up to set email alerts
|

From facilitation to competition: the effect of black locust (Robinia pseudoacacia L.) on the growth performance of four poplar-hybrids (Populus spp.) in mixed short rotation coppice

Abstract: Short rotation coppices play an important role in providing biomass for energetic use. Mixing fast-growing tree species in short rotation coppices may show complementarity effects and increased yield. The aim of this study was to analyze the effect of species interaction in mixed short rotation coppices with fast-growing Populus spp.-hybrids and the N-fixing Robinia pseudoacacia. Four different Populus-hybrids (AF2, Fritzi Pauley, Hybride 275 and Max 1), planted alternately in pure and mixed stands with R. pse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 49 publications
1
13
0
Order By: Relevance
“…pseudoacacia . In our previous work about mortality (Rebola‐Lichtenberg et al, 2019) and facilitation and competition (Rebola‐Lichtenberg et al, 2021) in mixed poplar‐black locust SRC, we came, however, to the conclusion that R . pseudoacacia affected the overall performance of poplar mostly negatively due to its advanced growth and dominance in the crown layer.…”
Section: Discussionmentioning
confidence: 58%
See 3 more Smart Citations
“…pseudoacacia . In our previous work about mortality (Rebola‐Lichtenberg et al, 2019) and facilitation and competition (Rebola‐Lichtenberg et al, 2021) in mixed poplar‐black locust SRC, we came, however, to the conclusion that R . pseudoacacia affected the overall performance of poplar mostly negatively due to its advanced growth and dominance in the crown layer.…”
Section: Discussionmentioning
confidence: 58%
“…Even though poplar showed lower performance in mixed culture with black locust (Figure 2; Tables 4 and 5; Rebola‐Lichtenberg et al, 2019, 2021), a significant non‐transgressive overyielding was observed for two mixtures ( P . ‘AF2’/ R .…”
Section: Discussionmentioning
confidence: 96%
See 2 more Smart Citations
“…Mixed stands of poplar and black locust have already been tested in several recent studies [22,[24][25][26][27][28][29][30][31]. Black cottonwood (Populus trichocarpa Torr.…”
Section: Introductionmentioning
confidence: 99%